2014
DOI: 10.1086/677370
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Stiffening in Pulmonary Hypertension: Cause or Consequence? (2013 Grover Conference Series)

Abstract: Recent studies have indicated that systemic arterial stiffening is a precursor to hypertension and that hypertension, in turn, can perpetuate arterial stiffening. Pulmonary artery (PA) stiffening is also well documented to occur in pulmonary hypertension (PH), and there is evidence that pulmonary vascular stiffness (PVS) may be a better predictor of outcome than pulmonary vascular resistance (PVR). We have hypothesized that the decreased flow-damping function of elastic PAs in PH likely initiates and/or perpet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 205 publications
(332 reference statements)
4
61
0
2
Order By: Relevance
“…The predominant distal vasodilator effect (RPA) of levosimendan with mild vasodilatory effect on CPA in the vessels from the PE animals could preserve the ventricular-arterial coupling and the proximal-distal PA coupling during the treatment of PE-induced PH through avoiding the increase of proximal arterial stiffness [7,22]. We have previously shown that proximal PA vasoconstriction induced by vascular smooth muscle activation improves both buffering and conduit function of the PA during acute PH mainly due to the increase in wall viscosity, preventing increased wall stiffness secondary to the recruitment of collagen fibers [23].…”
Section: Discussionmentioning
confidence: 99%
“…The predominant distal vasodilator effect (RPA) of levosimendan with mild vasodilatory effect on CPA in the vessels from the PE animals could preserve the ventricular-arterial coupling and the proximal-distal PA coupling during the treatment of PE-induced PH through avoiding the increase of proximal arterial stiffness [7,22]. We have previously shown that proximal PA vasoconstriction induced by vascular smooth muscle activation improves both buffering and conduit function of the PA during acute PH mainly due to the increase in wall viscosity, preventing increased wall stiffness secondary to the recruitment of collagen fibers [23].…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium provides a critical role as an intermediary between blood flow and the vessel wall, serving as an effective biological mechanotransducer that senses and converts hemodynamic forces to biochemical signals that regulate angiogenesis, inflammation, vascular tone, and wall structure (24). Others have previously implicated increased stiffness and hemodynamic stress as a major cause of EC dysfunction in other experimental settings (11,17).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes in cell surface, swelling and cohesion of ECs are one of the first structural changes visible,11 followed by neomuscularisation of the normally non-muscularised acinar arterioles and medial hypertrophy of pre-acinar arteries 7. Proximal medial hypertrophy increases proximal PA stiffness, reducing physiologic proximal flow damping 12. As a result, peak flow velocity and flow velocity variance are increased, amplifying the flow disturbance in the distal PAs12 (figure 1C,E, figure 2).…”
Section: Flow-induced Remodelling Of the Pulmonary Vasculature: A Seqmentioning
confidence: 98%